Teachers' Professional Improvement - Category, Reference, Practice - Grażyna Kosiba (University of Lower Silesia, 2012)
The research took place in the Małopolska region, Poland, and comprised 225 randomly chosen subjects employed in the different types of schools in villages, towns and cities. The evaluation of the teachers' engagement in their professional improvement was done by the analysis of the different domains of educational and conceptual activity of the teachers. For this purpose the questionnaire developed by the author of this paper was used. The results of the research show that the teachers' activity in training courses - compared to the previous decades - has considerably increased. Furthermore, the results show that this kind of courses that improves teachers' development set to directed to the instrumental aims in education, dominates in the teachers' self-education.